Preparation and Photocatalytic Activity of Attapulgite/WO3 Nanocomposites. Issue 10 (2nd October 2016) - Yu, C. F.; Zhu, Y. F.; Zhou, G. H.; Ding, H. Y.; Zhang, Y.
Abstract : To improve the photocatalytic performance of tungsten oxide, attapulgite, used as supporter and adsorbent, was combined with tungsten oxide nanoparticles to form a kind of new photocatalyst. The photocatalyst (attapulgite/WO3 ) was prepared in a mild condition at 60ºC in an attapulgite/WCl6 /ethanol/water system through alcoholysis and hydrolysis. The amount of WCl6 added in the chemical solution has an important influence on the morphology and structure of the products based on field emission scanning electron microscope and X-ray powder diffraction characterization. The photocatalytic activities of all the products were tested by degrading rhodamine B with the existence of H2 O2 . The result shows that the obtained attapulgite/WO3 nanocomposites have a great improvement in photocatalytic activity.